Practical Child Law for Social Workers: A Guide to English Law and Policy - Clare Seymour and others; SEYMOUR (Clare); SEYMOUR (Richard) (Los Angeles Sage Publications, 2013)
The English legal system in the area of social work with children and families can be bewildering and complex and it is vital therefore that any textbook on the subject uses case law, case studies and research to critically-engage social workers and students alike. This book does just that - by examining, and putting into clear practical context, the current law and policy relating to social work with children and families. A guide for both students on placement as well as Newly Qualified Social Workers (NQSWs) entering their first roles within children and families teams, Practical Child Law for Social Workers is essential reading for a fast-paced and complex area of social work.
Keywords: Social Labour Welfare Law